2022
DOI: 10.1101/2022.06.21.496987
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global epistasis and the emergence of ecological function

Abstract: The functions and services provided by ecosystems emerge from myriad interactions between organisms and their environment. The difficulty of incorporating this complexity into quantitative models has hindered our ability to predictively link species-level composition with ecosystem function. This represents a major obstacle towards engineering ecological systems for environmental and biotechnological purposes. Inspired by similar findings in evolutionary genetics, here we show that the function of ecological c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(57 citation statements)
references
References 57 publications
(159 reference statements)
7
50
0
Order By: Relevance
“…Can we extend this way of partitioning interactions to microbial consortia? In recent work, we have found that, indeed, the functional effects of adding a species to a consortium does often scale linearly with the function of the background consortium, in a way that is very similar to what has been observed in genetic systems (Díaz-Colunga et al, 2022).…”
Section: An Ecological Parallel To Global Epistasis and The Emergence...supporting
confidence: 74%
See 4 more Smart Citations
“…Can we extend this way of partitioning interactions to microbial consortia? In recent work, we have found that, indeed, the functional effects of adding a species to a consortium does often scale linearly with the function of the background consortium, in a way that is very similar to what has been observed in genetic systems (Díaz-Colunga et al, 2022).…”
Section: An Ecological Parallel To Global Epistasis and The Emergence...supporting
confidence: 74%
“…The existence of these global functional interaction patterns appears to be rather general in ecosystems as we also found them in plant and algal communities (Díaz-Colunga et al, 2022). Importantly, different species within a consortium tend to have different "Functional Effect Equations" describing their unique, global functional interaction patterns (Díaz-Colunga et al, 2022). How the particular global functional patterns exhibited by a species depend on its traits, as well as the traits of the species it interacts with, is still not well understood.…”
Section: An Ecological Parallel To Global Epistasis and The Emergence...mentioning
confidence: 69%
See 3 more Smart Citations